SISTEM REKOMENDASI PEMILIHAN KANDIDAT CALON TENAGA KERJA MENGGUNAKAN METODE PROFILE MATCHING (STUDI KASUS: SMK AL-MALIKUS SHOLEH) - Huda , Nurul; Sucipto , Hadi (Inovate, 2024)
Al-Malikus Sholeh Vocational High School recognizes the need to create a job candidate recommendation system that can connect applicants, partners, and administrators to facilitate the recruitment process for job candidates who are alumni of Al-Malikus Sholeh Vocational High School, partners as job suppliers, and administrators as intermediaries between applicants and partners in a system that will be developed. The decision support system is expected to greatly assist partners in selecting suitable human resources to fill vacant positions based on previous career planning. The profile matching method is used in the decision support system because it is easily understood and implemented, as it only relies on the compatibility between the candidate's profile and the ideal profile. This generates a list of candidates who closely match the ideal profile, making the selection process easier to identify the best candidate. The results of this study indicate that the Profile Matching method can be applied to evaluate and rank applicants, based on predetermined applicant data, job criteria, and subcriteria, before performing calculations. The testing results, both from manual calculations and calculations within the application system using the same input data, applicant data, criteria, and subcriteria, showed identical values and rankings. Therefore, the accuracy level of the calculations between manual and application system has the same results. Keywords: Decision Making System, Profile Matching, Alumni, Job Vacancies, Ranking.